A combinatorial approach to enhance barrier properties of thin films on polymers: Seeding and capping of PECVD thin films by PEALD. Issue 5 (8th March 2018) - Gebhard, Maximilian; Mitschker, Felix; Hoppe, Christian; Aghaee, Morteza; Rogalla, Detlef; Creatore, Mariadriana; Grundmeier, Guido; Awakowicz, Peter; Devi, Anjana
Abstract : A combinatorial approach to deposit gas barrier layers (GBLs) on polyethylene terephthalate (PET) by means of plasma‐enhanced chemical vapor deposition (PECVD) and plasma‐enhanced atomic layer deposition (PEALD) is presented. Thin films of SiOx and SiOx Cy Hz obtained from PECVD were grown either subsequently on a PEALD seeding layer (SiO2 ) or were capped by ultrathin PEALD films of Al2 O3 or SiO2 . To study the impact of PEALD layers on the overall GBL performance, PECVD coatings with high macro defect densities and low barrier efficiency with regard to the oxygen transmission rate (OTR) were chosen. PEALD seeding layers demonstrated the ability to influence the subsequent PECVD growth in terms of the lower macro defect density (9 macro‐defects mm −2 ) and improved barrier performance (OTR = 0.8 cm 3  m −2  day −1 ), while the PEALD capping‐route produced GBLs free of macro‐defects. Abstract : PEALD thin films of SiO2 and Al2 O3 are employed as ultrathin seeding and capping layers to enhance the gas barrier performance of coatings on PET via PECVD. PEALD coatings strongly improve both the macro defect density of PECVD coatings and thereby increase the barrier performance of the combined systems.